If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + -4) = -15 Reorder the terms: 3(-4 + n) = -15 (-4 * 3 + n * 3) = -15 (-12 + 3n) = -15 Solving -12 + 3n = -15 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 3n = -15 + 12 Combine like terms: -12 + 12 = 0 0 + 3n = -15 + 12 3n = -15 + 12 Combine like terms: -15 + 12 = -3 3n = -3 Divide each side by '3'. n = -1 Simplifying n = -1
| X*.38=112 | | 26x^2-130x+6=0 | | 4x^2-y^2=11 | | 14j+3k= | | X^2+x+1=2 | | 8x+2z=4+7y | | 5x+2.5y=840 | | 7p-10=-3p+5 | | 10p+5=5p-5 | | 12y+8=13y-18 | | 20-2x=x+8 | | x^2-10=350 | | 17=9y-5y-3 | | yl=14j+3k | | 11=-9x+5x | | 324÷1/8 | | 16N=2(N+12)+2N | | 5x+5=6y | | 7(x-9)=14 | | 2x+(5x-3y)= | | 16N=(N+12)+2N | | -1.8=.4x | | 3x+1=9x+7 | | -xln(4)+xln(8)=ln(3) | | 15s^3+35s^2+18s=-2s | | (3/7)/s=(1/3) | | ln(1+x)+ln(x-2)=ln(4) | | ln(a)=2.813585093 | | 5xy-3x-4y-1=0 | | ln(3+x)+ln(6-x)=ln(15) | | 2x+35=12x-5 | | 2kx+9=4x+kx |